Indonesia's New Capital City Development Strategy from Mobility Optimization Perspective - Benny Aristo; Ivan Kristianto Singgih; Suryadiputra Liawatimena (Proceeding of International Conference on Global Innovation and Trend in Economics, 2022)
Based on Indonesia's 2045 vision, Indonesia’s new capital city development is expected to accelerate Indonesia’s economic transformation. Its development consists of six economic clusters and two supporting clusters, including low carbon-energy targets, smart city, and industry 4.0. This study provides insights into achieving the stated development goals from the mobility optimization perspective. The strategies include optimization and machine learning-based traffic control, real-time and dynamic bus routing, smart waste management, and the use of drones and electric vehicles. This study can guide researchers and practitioners to contribute to Indonesia’s new capital city development and accelerate the process.